Profiling the perceived mangrove forest use value and community's willingness to pay for mangrove conservation - Sunoto, Yakin Nur; Abdul Aziz, Fatiah; Ponrahono, Zakiah; Mohamed Osman, Mariana (Malaysia Insitute of Planner, 2020)
A broad range of ecological services from mangrove forest encompasses a mixture of landward and seaward transition around tropical and subtropical areas in many regions that are threatened by humans. Among the issues highlighted in this research are i) the decline in mangrove areas due to development activities, and ii) zero price value of mangrove areas. This study reports on the direct use value of mangrove forest, willingness to pay for the conservation of mangrove forests, and satisfaction towards current mangrove management in Kampung Sungai Melayu, located at Johor state in Malaysia. A face-to-face survey was employed, targeting 111 heads of households and 219 individuals from the local community through a simple random sampling technique. This study concludes that the local community are willing to pay for mangrove conservation at RM17.84 per year. Based on the significant results from the Chi-Square analysis, three factors have a significant correlation with the “willingness to pay” for mangrove conservation which includes the length of residency (X2 = 11.780) and household income (X2 =13.463).